PENGEMBANGAN BUKU CERITA PENDEK SEBAGAI BAHAN AJAR ALTERNATIF UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MATERI SISTEM IMUN - Nafisah, Muklinatun Sofa; Prajoko, Setiyo; Sukmawati, Ika (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Learning is a system designed to support the student learning process. Teachers play a key role in enhancing learning success by fostering student motivation, one of which can be achieved through the use of effective teaching materials. This study aims to determine the feasibility and effectiveness of short story books as alternative teaching materials to improve learning motivation in the immune system topic. This research employed a Research and Development (R&D) approach using the ADDIE model, which includes the following stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Data were collected through interviews and questionnaires. The instruments included interview guides, validation sheets from subject matter experts, media experts, and short story experts, as well as student motivation questionnaires. The feasibility results of the developed short story book showed a validation score of 73.00% from material experts, 82.14% from media experts, and 89.81% from short story experts. At the implementation stage, student motivation results reached 80.95%, with an N-Gain score of 0.50. These findings indicate that the short story book is feasible and effective as an alternative teaching material to enhance students' learning motivation.